Phalaropus fulicarius (Phalaropodidae) - Brüten - Georg Rüppell (IWF (Göttingen), 1968)
(en)The film shows a brooding male Phalaropus fulicarius. To be seen are brood movements, and the bird preening itself, and sleeping. Phalaropus fulicarius